2022
DOI: 10.1186/s12905-021-01572-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of women's traditional gender beliefs in depression, intimate partner violence and stress: insights from a Spanish abbreviated multicultural measure

Abstract: Background Research on traditional gender beliefs has highlighted their psychological impact and social implications for women. The purpose of this study was twofold. First, we aimed to adapt and validate the Spanish version of the Multicultural O’Kelly Women’s Beliefs Scale. Next, we explored its sources of validity evidence in relation to intimate partner violence, stress, and depression. Based on the Rational Emotive Behavior Therapy framework, traditional gender beliefs were expected to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…The social role theory has highlighted that male and female expectations related to social roles are a product of socialisation (Eagly and Wood, 2016; Rovira et al , 2022; Schneider and Bos, 2019). Considering the social roles where men are the “providers”, job security becomes vital for them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The social role theory has highlighted that male and female expectations related to social roles are a product of socialisation (Eagly and Wood, 2016; Rovira et al , 2022; Schneider and Bos, 2019). Considering the social roles where men are the “providers”, job security becomes vital for them.…”
Section: Resultsmentioning
confidence: 99%
“…Human behaviours are formed and sustained through socialisation (Eagly and Wood, 2016;Schneider and Bos, 2019). According to the gender role theory, those who hold the traditional view of social roles believe that women are caregivers while men are providers (Ngo et al, 2014;Rovira et al, 2022;Sirror et al, 2021). Indonesia still holds traditional gender views (Bird et al, 1984;Daraba et al, 2021;Mintz and Mahalik, 1996).…”
Section: Indirect Effect Of Abusive Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the gender intensification hypothesis, those who internalise traditional gender norms (femininity or masculinity) may experience more psychological pressure, which induces gender role stress ( Tolman et al, 2006 ). It has been demonstrated that conformity to masculine/feminine gender identity is associated with poor mental health in both sexes ( Herreen et al, 2021 ; Rovira et al, 2022 ; Seidler et al, 2016 ). Our study found that this effect was significantly associated with depressive symptoms and poor subjective health in married women, especially when the GRAs were related to gender role differences in economic participation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, men who conform to masculine norms have a tendency to consume more meat and women who conform to feminine norms have a higher risk of eating disorders due to their striving for thinness ( Fleming & Agnew-Brune, 2015 ; Sloan et al, 2015 ). In addition, traditional gender identity has been found to be associated with an increased risk of depression in women ( Rovira et al, 2022 ). Furthermore, studies have shown that gender role stress occurs when an individual's preferences or behaviours conflict with one's own gender-related stereotypes, and this stress is associated with psychiatric problems such as eating disorders and depression ( Bekker & Boselie, 2002 ; Kuehner, 2003 ).…”
Section: Introductionmentioning
confidence: 99%